Preliminary temporal characteristics of spectral lines emission from PF-1000 discharges by means of MECHELLE®900 spectrometer - Skladnik-Sadowska, E.; Sadowski, M.J.; Malinowski, K.; Tsarenko, A.V.; Tereshin, V.I.; Scholz, M.; Paduch, M.; Tomaszewski, K. (Вопросы атомной науки и техники, 2005)
The paper presents results of time-resolved spectroscopic measurements of pulsed plasma streams generated in PF-1000 facility. The use was made of a MECHELLE-900 optical spectrometer, which made possible measurements within the wavelength range from 200 nm to 1100 nm, with exposition times ranging from 100 ns up to 50 ms. Particular attention was paid to investigation of the spectral lines of the Balmer series from the working gas ions (i.e. Dα, Dβ, Dγ) and some impurity lines. It is importance not only for estimates of plasma parameters, but also for application-oriented studies. У роботі представлені результати спектроскопічних вимірів з дозволом за часом імпульсних плазмових потоків, генерируємих на установці PF-100. Перевага була віддана оптичному спектрометрові MECHELLE-900, що дозволяє проводити виміри в межах довжин хвиль від 200 nm до 1100 nm з експозицією часу в інтервалі від 100 ns до 50 ns. Особлива увага була приділена дослідженню спектральних ліній Бальмеровської серії для іонів робочих газів (тобто Dα, Dβ, Dγ) і деяких ліній домішок. Це важливо не тільки для оцінки параметрів плазми, але і для прикладних досліджень. В работе представлены результаты спектроскопических измерений с разрешением по времени импульсных плазменных потоков, генерируемых на установке PF-100. Предпочтение было отдано оптическому спектрометру MECHELLE-900, который позволяет проводить измерения в пределах длин волн от 200 nm до 1100 nm с экспозицией времени в интервале от 100 ns до 50 ns. Особое внимание было уделено исследованию спектральных линий Бальмеровской серии для ионов рабочих газов (т.е. Dα, Dβ, Dγ) и некоторых примесных линий. Это важно не только для оценки параметров плазмы, но и для прикладных исследований.